An evaluation of sodium zirconium cyclosilicate: a new treatment option for hyperkalaemia in China. (11th February 2023) - Lu, Yuan; Liu, Bi-Cheng; Liu, Hong
ABSTRACT: Introduction: Hyperkalemia is a common complication of chronic kidney disease (CKD), diabetes mellitus (DM), and heart failure (HF) that can lead to severe arrhythmias and sudden death and is associated with a higher risk of mortality. Therefore, the prevention and treatment of hyperkalemia is important. Sodium zirconium cyclosilicate (SZC), a new oral potassium-lowering drug, has offered an additional treatment option for Chinese patients with hyperkalemia since its launch in China in late 2019, and some experience has been accumulated regarding its efficacy and safety. Areas covered: In this review, the authors summarize the epidemiological features of hyperkalemia in China and review the clinical data regarding the use of sodium zirconium cyclosilicate in Chinese patients. Expert opinion: The prevalence of hyperkalemia is particularly high in Chinese patients with chronic kidney disease and heart failure. In China, recent clinical studies have shown that SZC rapidly reduces serum potassium, maintains normal potassium concentration, and is well tolerated and safe. Two Chinese expert consensus statements have recommended the use of SZC for the acute correction and chronic maintenance of potassium concentration.